Démarche d'investigation et problématisation en mathématiques et en SVT : des problèmes de démarcation aux raisons d'une union - Magali Hersant; Denise Orange-Ravachol (Nantes Université, 2015)
In France, the recent curricula for mathematics, science and technology promote primary and middle school students' engagement in investigative approaches. These approaches are supposed to contribute to the internalization of common skills. How is it possible for the same approach to unite both mathematics and science? Our paper shows that the differences between these disciplines stressed by the institution (experimentation, validation methods) are problematic. It also studies the possibility to combine these fields by considering the construction of knowledge they operate as problematizations.